Correction: Brandl and Schrader (2024). Student Player Types in Higher Education—Trial and Clustering Analyses. Education Sciences, 14(4), 352 - Lea C. Brandl; Andreas Schrader (Education Sciences)
The originally published version of this paper (Brandl & Schrader, 2024) contains an error in Figure 4 regarding the appropriate mechanics [...]